Foliar Application of a Mixture of Amino Acid-Based Growth Promoters Enhances Tomato Seedling Production - Alexander Calero Hurtado; Jorge Félix Meléndrez Rodríguez; Kolima Peña Calzada; Yanery Pérez Díaz; Alay Jiménez Medina (Horticulturae)
A mixture of amino acids, including aspartic acid, arginine, glycine, and tryptophan, can effectively promote tomato seedling growth. This research aimed to evaluate how the foliar spraying of an amino acid mixture, applied at various doses and intervals, influences the growth of tomato seedlings in a traditional seedbed. An experiment was conducted in the field, with the treatments distributed in a factorial arrangement (3 × 2) in a completely randomized block design with five replications. The growth parameters of tomato seedlings were improved by combining three doses of the amino acid mixture (0.25, 0.50, and 0.75 L ha−1 as VIUSID® agro) with two application intervals (weekly and biweekly). Results indicated that the foliar application of an amino acid mixture at 0.25 L ha−1 weekly enhances stem thickness, stem length, root length, leaf area index, root, shoot, and total dry biomass accumulation. Therefore, investing in the production of robust and high-quality tomato seedlings can lead to improved establishment, faster growth and development, reduced losses, and earlier and higher yields. This discovery indicates that using weekly low doses of the mixture of amino acids could be an effective and environmentally friendly option for improving tomato seedling production in traditional seedbed conditions.